THE STUDENTS’ DIFFICULTIES ON THE USE OF ADJECTIVE PHRASE IN WRITING ENGLISH TEXT - Sarmadani; St Asriati AM; Ilmiah (Journal of Language Testing and Assessment, 2021)
This study aimed at finding out: (1) What are the students’ difficulties on the use of adjective phrase in writing English text, (2) What are the factors that make students difficult in writing adjective phrase. The method of this research was descriptive quantitative method. Based on the results researcher found the students’ difficulties on the use adjective phrases those are intralingua error and interlingua error. Intralingua error consisted of 41 items or,87.23% students have difficulty in intralingua errors, while interlingua error consisted of 6 items or 12.76% students have difficulty in interlingua errors. Based on the types of adjective phrases, there were 12 items or 25.53% of students have difficulty using predicative adjectives and there were 35 items or 74.46% of students having difficulty using attributive adjectives. The factors that make difficult for students to write adjective phrases in writing are grammatical weaknesses, knowledge, understanding, lack of training and educational background. It can be concluded that there were two students’ difficulty on the use of adjective phrase and 4 factors that make students difficult to make adjective phrase.